To the question about the therapeutic tactics in patients with cerebral supratentorial stroke - L.O. Shevchenko; V. I. Bobrova; V. M. Kalashnik (Patologìâ)
The vascular diseases of brain grew considerably in the economic developed countries, what stipulates the actuality of this problem.